Proteomic Approaches for the Global Analysis of Proteins - Gregory A. Michaud; Michael Snyder (BioTechniques)
Improvements in technology that allow miniaturization and high-throughput analyses of thousand of genes and gene products have changed the focus and scope of research and development in both academia and industry. It is now possible to study entire proteomes with the goals of elucidating protein expression, subcellular localization, biochemical activities, and their regulation. Alterations in different cell types and conditions and in normal and disease states can be revealed. This wealth of information not only has facilitated our basic understanding of many biological processes but also has enormous potential for drug discovery and development.